Factors Influencing Accounting Students' Interest in Taking Accounting Certification: Case Study of Final Semester Accounting Students at Universities in Besuki Residency - Rifana, Tasya Dila (Westscience Press, 2024)
Indonesia has a small number of public accountants and still needs a large number of professions, in anticipation of the expansion of the business sector. The number of CA graduates in East Java is still low compared to the number of accounting graduates every year. This is due to the relatively high enrolment costs, the lack of training for students on the purpose and benefits of having a Chartered Accountant (CA) certification itself. The research aims to find out the impact of career motivation, level of understanding, and cost perception on obtaining accounting certification. This research uses a quantitative approach, with the aim of testing the hypothesis. The population in this study is a student of the S1 Accounting Final Semester Program at Besuki Se-Karesidenan College. Sampling using probbalility sampling. Data analysis using the help of the IBM SPSS Statistics application. Research results show that career motivation and level of understanding influence the level of comprehension of the interest of students taking accounting certification. While the perception of costs has no influence on the interest of students taking accounting certification.